Antibiotic prophylaxis for infective endocarditis: a systematic review and meta-analysis. Issue 12 (17th February 2017) - Cahill, Thomas J; Harrison, James L; Jewell, Paul; Onakpoya, Igho; Chambers, John B; Dayer, Mark; Lockhart, Peter; Roberts, Nia; Shanson, David; Thornhill, Martin; Heneghan, Carl J; Prendergast, Bernard D
Abstract : Objective: The use of antibiotic prophylaxis (AP) for prevention of infective endocarditis (IE) is controversial. In recent years, guidelines to cardiologists and dentists have advised restriction of AP to high-risk groups (in Europe and the USA) or against its use at all (in the UK). The objective of this systematic review was to appraise the evidence for use of AP for prevention of bacteraemia or IE in patients undergoing dental procedures. Methods: We conducted electronic searches in Medline, Embase, Cochrane Library and ISI Web of Science. We assessed the methodological characteristics of included studies using the Strengthening the Reporting of Observational Studies in Epidemiology criteria for observational studies and the Cochrane Risk of Bias Tool for trials. Two reviewers independently determined the eligibility of studies, assessed the methodology of included studies and extracted the data. Results: We identified 178 eligible studies, of which 36 were included in the review. This included 10 time-trend studies, 5 observational studies and 21 trials. All trials identified used bacteraemia as an endpoint rather than IE. One time-trend study suggests that total AP restriction may be associated with a rising incidence of IE, while data on the consequences of relative AP restriction are conflicting. Meta-analysis of trials indicates that AP is effective in reducing the incidence of bacteraemia (risk ratio 0.53, 95% CI 0.49 to 0.57, p<0.01), but case–control studies suggest this may not translate to a statistically significant protective effect against IE in patients at low risk of disease. Conclusions: The evidence base for the use of AP is limited, heterogeneous and the methodological quality of many studies is poor. Postprocedural bacteraemia is not a good surrogate endpoint for IE. Given the logistical challenges of a randomised trial, high-quality case–control studies would help to evaluate the role of dental procedures in causing IE and the efficacy of AP in its prevention.